Economics of waste prevention: Second-hand products in Germany - Henning Wilts; Marina Fecke; Christine Zeher (Economies, 2021)
Reuse is still seen as a "niche phenomenon" and consumers seem to waste economic opportunities linked to buying and selling second-hand products. For this reason, this paper focuses on incentives and barriers to sell and buy second-hand products, as indicated in the literature, and applies a theoretical framework of transaction costs to explain the existing consumption patterns. For this paper, a representative online survey was conducted in which 1023 consumers in Germany participated, age 16 and older. The data were analyzed for statistically significant deviations between different groups of economic actors selling or buying second-hand products. Results show that valuable unused products exist in households, but barriers such as uncertainties about the reliability of the buyer or the quality of the product hinder the transition into sustainable consumption. Different forms of transaction costs are important explanatory variables to explain why consumers nevertheless predominantly buy new products, although they are aware that second-hand would save money and make an individual contribution to climate protection.
Keywords: 330; circular economy; reuse; second-hand; transaction costs